Brucellosis Outbreak in China, 2019 - Shah Marzia Mahjabin Lina; Mohana Priya Kunasekaran; Aye Moa (University of New South Wales, 2021)
During late July to August 2019, Zhongmu Lanzhou biopharmaceutical plant of Gansu province was producing brucella vaccine for animals and reportedly used an expired disinfectant for cleaning, which failed to kill all the bacteria. At the same time a leak occurred in the plant, which allowed the contaminated waste in the form of aerosol to be leaked in the air. This caused the first outbreak in the Lanzhou animal research institute as the contaminated aerosols were carried and spread there. Community transmission took place after this event. The infection has so far been confirmed in 10,528 people after testing - 68571 people up to November 30, 2020.